Pattern of Presentation among patients of Conversion Disorder reporting to the Department of Psychiatry and Behavioral Sciences, Jinnah Post Graduate Medical Center, Karachi Pakistan - Taufiq, Fatima; Afridi, M. Iqbal; Lal, Chuni; Khan, Mohammad Ashar Waheed; Qureshi, Saima; Haider, Syed Zafar (Journal of Pakistan Psychiatric Society, 2016)
Abstract